THE EFFECTIVENESS OF USING ART IN ENHANCING ENGLISH LANGUAGE PROFICIENCY - Abduvalieva Jasmina Jahongir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the use of art-based activities and materials in enhancing English language proficiency. Drawing from existing research, it explores how the integration of visual arts, performing arts, and other creative mediums can positively impact the development of listening, speaking, reading, and writing skills in English language learners. The article discusses the theoretical foundations and pedagogical approaches that underpin the use of art in English language instruction. It also presents case studies and empirical findings that demonstrate the efficacy of art-integrated language learning programs. The article concludes by highlighting best practices and offering recommendations for further research in this area.